1799 Terr. of Miss. Laws 113 - (:unkn) unknown (My University, 1799)
A Law for The Regulation of Slaves: Prohibited any "Negro or mulatto" from carrying gun, powder, shot, club, or other weapon. Also prohibits a "negro or mulatto" from possessing a gun, weapon, or ammunition.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES